2016
DOI: 10.5114/pdia.2015.48052
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of sleep-related breathing disorders in patients with chronic urticaria at its asymptomatic or oligosymptomatic stages

Abstract: A b s t r a c tIntroduction: Chronic urticaria (CU), in view of its manifestations (pruritus, wheals), chronic and recurrent nature is very bothersome for patients and significantly influences their quality of life. Aim: To assess the importance of sleep problems and sleep-related breathing disorders (SRBDs) declared by CU patients, for their quality of life. Material and methods: Twenty-eight patients with CU at an asymptomatic stage or with minimal symptoms and signs were qualified for the study. In these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
4
7
0
1
Order By: Relevance
“…In other words, the examined group of CU patients manifested worsened QoL. This observation is in agreement with literature data [ 16 , 18 , 27 30 ]. The above seems to be explained by an unpredictable course of CU, recurrent disease episodes and the location of skin lesions (on visible body parts).…”
Section: Discussionsupporting
confidence: 93%
“…In other words, the examined group of CU patients manifested worsened QoL. This observation is in agreement with literature data [ 16 , 18 , 27 30 ]. The above seems to be explained by an unpredictable course of CU, recurrent disease episodes and the location of skin lesions (on visible body parts).…”
Section: Discussionsupporting
confidence: 93%
“…11,12 Patients with chronic urticaria report frequent sleep awakenings and difficulty falling asleep, with daytime fatigue reported by 75% of the patients and a higher incidence of sleep-related breathing disorder compared with the general population. 13 The resulting daytime fatigue, mood depression, and lower efficiency at school or work also impair these patients. 14…”
Section: Discussionmentioning
confidence: 99%
“… 11 Another study by Perkowska and colleagues reported that around 25% of participants with CSU had sleep related breathing disorders, a higher rate compared to the general population. 12 Interestingly, when compared to another dermatologic disease, a higher proportion of CU patients reported sleep difficulties compared to psoriasis patients. 3 …”
Section: Introductionmentioning
confidence: 98%